Oblique sliding ulna osteotomy to treat paediatric neglected monteggia fracture dislocation - Nik Abdul Adel, Nik Alyani; Mohd, Emil Fazliq; Munajat, Ismail; Sulaiman, Abdul Razak (SAGE Publications Ltd, 2024)
Introduction: There have been osteotomy methods that corrected or overcorrected the ulna deformity as part of surgical treatment for chronic radial head dislocation.